Electrical characteristics of conductive ultrathin bonded wearing course for active deicing and snow melting. Issue Volume 20:Issued 11(2019) (2nd November 2019) - Sun, Daquan; Sun, Guoqiang; Zhu, Xingyi; Xiao, Feipeng; Dai, Ziwei; Liu, Fuliang
ABSTRACT: Active deicing and snow melting technologies, such as conductive asphalt concrete and heating cable, have got extensively concerned, however they are not applicable to the existing roads. Therefore, the conductive ultrathin bonded wearing course (CUBWC) is proposed, which mainly consists of the conductive functional layer (CFL) and gravel wearing course. The CFL is prepared by blending the graphite, carbon fibre (CF) and epoxy resin adhesive. To get the optimal electrical characteristics of CUBWC, the effects of CF length, CF content and graphite content on the resistivity of CFL were measured. The temperature sensitivity test and the temperature cycling test were further conducted to evaluate the temperature sensitive property and stability of CUBWC. Finally, the optimal contents of the graphite (25% by mass) and CF (4% by mass) were determined by considering the effective electrical conductivity and temperature stability of CUBWC.